Sosialisasi Perancangan Redesain MAP Rekam Medis di Puskesmas Bestari - Theresia Hutasoit; Mei Sryendang Sitorus (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
A medical record folder is a thick paper cover that unites all of a patient's sheets so that they become one complete history, protects the medical record files inside so that they are not easily damaged and makes it easier to store, search and transfer medical record files (Heltiani, 2020). Designing a medical record folder has physical aspects, anatomical aspects and content aspects. The physical aspect consists of materials: Ivory paper, the shape resembles a rectangular book, there are folds to increase the capacity to store medical record forms accompanied by color coding. Anatomical aspects include the Header, which contains the logo, name, address and telephone number, Introduction, Instructions, which contains confidential information from the medical record folder, Body contains the Name and Medical Record Number. Register Number and Year of Visit, Font using Time New Roman, form title size 40, patient identity and year of visit size 12, while Arial font size 14 is used for instructions, Ruler has a ruler on the medical record folder to limit the heading and body of the map, Border there is a border in the medical record folder. Content aspects include the identity of the health service facility, the identity of the name of the health service facility, the patient's name, the medical record number, the year of the last visit and the row available in the year of the last visit in the medical record folder. Socialization is given to medical record officers using discussion, lecture and question and answer methods. It is hoped that the results of this socialization will be for the Bestari Community Health Center to redesign the medical record folder which refers to three aspects, namely: anatomical aspects, physical aspects and content aspects so that the medical record forms are not damaged or scattered.